Study in the Use of Cheiloscopy for Sex Determination in the Population of Eastern Odisha: An Observational Study - Dehury Manoj Kumar; Subal Kumar Naik; Praveena; Rajashree Biswal (Student's Journal of Health Research Africa, 2026)
Human identification is a fundamental aspect of forensic science, particularly in situations involving mass disasters, criminal investigations, and unidentified human remains. While fingerprints and DNA profiling remain the gold standards for personal identification, lip-print analysis (cheiloscopy) has gained increasing attention as a supplementary forensic tool because the grooves and wrinkles on the vermilion border of the lips are considered unique and relatively stable throughout life. Several studies have suggested that lip-print patterns may exhibit sexual dimorphism, making cheiloscopy a potentially valuable method for sex determination. However, regional variations in lip-print characteristics necessitate population-specific investigations. Objectives The study was undertaken to determine the distribution of lip-print patterns among individuals from the Eastern Odisha population, compare the distribution of these patterns between males and females, and evaluate the usefulness of cheiloscopy as an adjunctive method for forensic sex determination. Methods An observational study was conducted over a period of three years among 150 adult participants from SCB Medical College & Hospital, Cuttack, Odisha. Lip impressions